Tamil Schools Donation System - Ramoo, Thiveyarupan (IRC, 2020)
The present invention provides a method and system that electronically collects donations from donor individuals and organizations and distributes these collected funds to schools from rural area and the schools with poor facilities. The donor will supply information related to the identity of the designated recipient organization, the amount or percentage of the donation and the frequency of the donations. At designated donation intervals, the specified or calculated monetary amount is transferred from the donor account to the system. The funds are then transferred to the recipient account by the system once verified. At the completion of this transfer, both the donor and the recipient school can receive verification of the amount of the transfer. During the time interval between transfers from the donor account, the donor can modify the information that controls the amount of a monetary transfer and the frequency of the transfers from the donor account.